A Modified Constitutive Model for the Description of the Flow Behavior of the Ti-10V-2Fe-3Al Alloy during Hot Plastic Deformation - Fukang Wang; Jingyuan Shen; Yong Zhang; Yongquan Ning (Metals, 2019)
The hot deformation behavior of the aerospace Ti-10-2-3 alloy was investigated by isothermal compression tests at temperatures of 740 to 820 °C and strain rates of 0.0005 to 10 s−1. The results show that the studied alloy is extremely sensitive to deformation parameters, like the temperature and strain rate. The temperature mainly affects the magnitude of flow stress at larger strains, while the strain rate not only affects the value of flow stress but also the shape of the flow curves. At low strain rates, the flow stress increases with strain, followed by a broad peak and then remains almost constant. At high strain rates, the flow curves exhibit a hardening to a sharp peak at small strains, followed by a rapid dropping to a plateau caused by dynamic softening. In order to describe such flow behavior, a constitutive model considering the effect of deformation parameters was developed as an extension of an existing constitutive model. The modified constitutive model (MC) was obtained based on the original constitutive model (OC) by introducing a new parameter to compensate for the error between the experimental data and predicted values. Compared to the original model, the developed model provides a better description of the flow behavior of Ti-10-2-3 alloy at elevated temperatures over the specified deformation domain.